Role of negative pressure in structural responses of gravity dams to underwater explosion loadings: The need to consider local cavitation. (April 2021) - Zhang, Qi-Ling; Hu, Ying-Guo; Liu, Mei-Shan; Li, Duan-You
Highlights: Negative pressure is significant near the dam face without cavitation considered. The negative pressure produces overestimated tensile damage to the dam face. The negative pressure produces underestimated tensile damage to the dam base. The local cavitation prevents exaggerated negative pressure acting on the dam face. The cavitation threshold has a significant influence on the response of the dam. Abstract: Negative pressure tends to occur at a fluid–structure interface (FSI) in an underwater explosion (UNDEX) event. When the pressure drops to a value of vapor pressure, distributed cavities will form and maintain the pressure acting on the FSI during expansion, i.e. the local cavitation phenomenon. The local cavitation phenomenon is likely to occur at a dam-water interface when the dam is undergoing an UNDEX impact. It should significantly change the hydrodynamic-pressure distribution on the dam face and thus have an important influence on the response of the dam. Unfortunately, far too little attention has been paid to local cavitation in the current UNDEX resistant design and evaluation of dams. In this work, a dynamic analysis of a 72.12-m-high gravity dam (non-overflow monolith) undergoing an UNDEX impact is carried out with ABAQUS/Explicit. The ability of the employed software to capture the negative pressure at a FSI in an UNDEX event is validated by comparing the simulated pressure history at a water-plate interface with the analytical solution and experimental data reported in the literature. The simulation shows that significant negative pressure would arise at the dam-water interface without a zero-value cavitation limit considered. The negative pressure would produce overestimated tensile damage to the dam face but underestimated one to the dam base. A more reasonable prediction of the hydrodynamic-pressure distribution on the dam face should be obtained when the local cavitation effect is considered, which prevents the dam face from undergoing exaggerated negative pressure. It is therefore suggested that the local cavitation effect should be considered in future UNDEX resistant design and evaluation of dams, however, with cautious use of the cavitation threshold.